Pengaruh Spray Minyak Atsiri Kulit Kayu Manis (Cinnamomum burmannii) terhadap Daya Tolak Nyamuk Aedes aegypti - Yolla Ayu Medikawanti; Sarjito Eko Windarso; Agus Kharmayana Rubaya (Buletin Keslingmas, 2026)
Dengue Hemorrhagic Fever (DHF) transmitted by Aedes aegypti mosquitoes remains a significant health issue in Indonesia. While synthetic repellents such as DEET are effective, they carry risks of skin irritation and environmental impact. Essential oil from cinnamon (Cinnamomum burmannii), containing compounds like cinnamaldehyde and eugenol, shows potential as a safer natural repellent. This study aimed to investigate the effect of varying concentrations of cinnamon essential oil spray on the repellent efficacy against Aedes aegypti mosquitoes and to determine the concentration most effective at repelling mosquitoes. An experimental post-test only control group design was employed, using three spray concentrations (5%, 10%, 15%) with six repetitions per group. The repellent data obtained were tested for normality and homogeneity and then analyzed using one-way ANOVA, followed by Tukey HSD post hoc test. The average mosquito repellent efficacy observed was 62% at a 5% concentration, 70% at 10%, and 85% at 15%. One-way ANOVA results indicated significant differences among the three concentrations (p < 0.001). Tukey HSD further confirmed that the 15% concentration had a significantly higher efficacy compared to the other two concentrations. However, this concentration also produced a stronger and longer-lasting heat sensation on the skin, making it less comfortable for users.